Trend and Development of Soccer Research: An Observation - Muhammad Shahidul Islam (Program Pascasarjana Universitas Negeri Jakarta, 2023)
The game of soccer has been adopted by nearly every nation and it is one of the most decentralized sports in the world. Due to the popularity of soccer, several research studies on football’s performance have been conducted to satisfy the people’s interest. This systematic qualitative research used both online and offline approaches to compile the literature. Therefore, the current researcher would like to conduct an investigation that necessitates a study of soccer literature’s trends and development. The primary objective of this academic qualitative study was to examine soccer-specific skills, system and formation-based soccer studies, somatotype research in soccer, fitness research in soccer, wearable Global Positioning System (GPS) technology in soccer game, and drone technology in soccer game. The relationship between manual digit ratio (2D:4D) and soccer is also discussed, as well as how the prenatal testosterone hormone can affect soccer performance. Researchers discovered that today’s soccer game is more dynamic than previous types of soccer. The efficiency of skills is typically dependent on early decision making. The previous researchers have discussed new ways and methods for improving soccer performance. Since the issue is so extensive, the present researcher believes that more scientific research on soccer’s trend and development is required.